Encyclopaedia of SAARC : vol.3; SAARC : the summits - Sharma, S.K., ed.; Kumar, Madhurendra, ed. (New Delhi : Pragun Publications, 2006)
General Collection
Keywords: Encyclopaedia; SAARC; SAARC - Summits